Efficacy and safety of a B-cell-driven rituximab regimen for the treatment of refractory idiopathic membranous nephropathy - Kaiqi Guo; Huaxia Zhu; Xingcheng Xu; Lanlan Huang; Huimin Li; Xiaowei Li (BMC Pharmacology and Toxicology)
Abstract Background Rituximab (RTX) is known to be effective in the treatment of idiopathic membranous nephropathy (IMN), but the specific dosing regimens have not been standardized. The aim of this retrospective study was to assess the clinical efficacy and safety of a B-cell-driven RTX regimen for the treatment of refractory IMN. Methods The data of 24 refractory IMN patients who underwent a B-cell-driven RTX regimen at Fuyang People’s Hospital of Anhui Medical University between October 2018 and November 2021 were retrospectively analysed. Results In total, 24 patients, comprising 17 males, with a mean age of 52.17 ± 8.28 years, were enrolled. After treatment with the B-cell-driven RTX regimen, 4 (16.67%) patients achieved complete remission, 11 (45.83%) patients achieved partial remission, the overall treatment efficacy was 62.50%, and there were 4 (16.67%) cases of relapse. The cumulative remission RTX dose was 2.40 g (IQR, 2.10 to 3.50), and the total cumulative RTX dose was 2.85 g (IQR, 2.40 to 4.20). B-cell depletion was achieved in 23 (95.83%) patients after the first dose of RTX was applied and in 1 patient after the second dose of RTX was applied. There was a significant difference in clinical remission between patients with and without a change in anti-PLA2R antibody status from positive to negative (P < 0.001). Two (8.33%) patients experienced infusion reactions, and 5 (20.83%) patients experienced nonserious infections. Treatment was discontinued in one patient due to severe pneumonia. Conclusion A B-cell-driven RTX regimen can induce partial or complete remission in patients with refractory IMN and is safe. Clinical trial number Not applicable.